Sociolinguistic styles - Hernandez Campoy, Juan Manuel (Chichester, West Sussex, United Kingdom Wiley-Blackwell, 2016)
"Sociolinguistic Styles systematically examines the complex phenomenon of style-shifting in sociolinguistics, focusing on its nature and social motivations, as well as on the mechanisms for its usage and its effects"--Provided by publisher.
Includes bibliographical references (pages 192-220) and index.
Keywords: Rhetoric -- Social aspects; Discourse analysis -- Social aspects; Language and logic; Sociolinguistics